The use of computer aided design for prototyping: an Approach to enhance competitiveness in ceramics production. - Olalere, Folasayo Enoch (2013)
While many manufacturers easily accept that eliminating physical prototypes in ceramics production equates to shorter or shortened product development cycle times. The reality, however, is that some manufacturers feel there are still valid reasons to keep physical prototypes in the design loop. So, while the use of physical prototypes is still a necessity for many product developers, replacing more physical prototyping and testing with digital modelling and simulation is seen as an approach that can enhance product competitiveness by reducing cost, development cycle time and also improve prototype quality. Therefore, this research practically investigates on how the use of computer aided design (CAD) can reduce development time, development cost and also improve prototype quality in ceramic product development. An experimental approach was used, by first investigating and analysing the conventional method used by ceramics manufacturers in product development. This was achieved with several visits to three ceramic factories in Kelantan, Malaysia. After which a digital method was developed by introducing computer aided design (CAD) into three stages in development process.